Sistem Pengelolaan Rekam Medis (Studi Kualitatif Di Puskesmas Tamalate Makassar Tahun 2019) - Maliang, Muhammad Iqbal; Imran, Ali; Alim, Andi (Window of Health : Jurnal Kesehatan, 2019)
Medical records are files that contain of notes and documents about patient identity, examination, treatment, actions and other services have been provided to patients. The medical records problem at Tamalate Health Center is the difficulty in processing data such as scattered medical record files, in addition to that medical record data stored on storage is increasing and piled up so it needs a lot of space. The amount of medical record data stored is sometimes misplaced in its place, causing difficulties for officers to find the medical record files. This research aims to obtain in-depth information about Medical Record Management System at Tamalate Health Center Makassar in 2019, includes naming system, numbering system, storage system, and medical record transport system. This study used qualitative research conducted at the Tamalate Health Center in Makassar on May 2019. Based on result of the research, it is obtained that the medical record system management at Tamalate Health Center Makassar, its naming system uses two syllables and written based on patient identity. Its numbering system is conducted in units (Unit Numbering System) where the patients only give a number for the next visits. The medical record storage system uses a centralized system which is the combination of the outpatient and emergency medical record. The medical record transport system is carried out by medical records officers by hand, trolley and cardboard. The need to add more rooms for medical record storage also storage shelf needs to be added so that medical storage staffs do not have difficulties with small room and give good facility to medical records staffs to do transport of medical record files so as not to use their hands.